Are International Students Getting a Bang for their Buck? : The Relationship between Expenditures and International Student Graduation Rates - Schmidt, Anthony (Journal of International Students, 2020)
An increasing number of US universities are recognizing the importance of international students. As state subsidies for public higher education institutions remain low, the reliance on out-of-state tuition from international students underscore their importance. Because international students often pay such high tuition fees, it is worth studying how such fees impact their education. This study investigated to what extent institutional expenditures affect undergraduate international student graduation rates. Using OLS regression with robust standard errors, the results indicated that academic support expenditures are significantly related to international student graduation rates, but may have a minimal effect. In addition, out-of-state tuition was also found to be significant, suggesting tuition affects students in ways not captured by expenditure data.